PENGARUH RISK PROFILE, GOOD CORPORATE GOVERNANCE EARNING, CAPITAL (RGEC) DAN MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN: STUDI KASUS PADA INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA SELAMA PANDEMI COVID-19 - Astuti, Iis Putri; Djajanti, Atik (Universitas Gunadarma, 2024)
This research aims to examine the influence of the level of bank health using the RGEC component which consists of credit risk, operational risk, liquidity risk, good corporate governance, earnings and capital as well as earnings management on the value of companies in the banking industry listed on the Indonesia Stock Exchange (IDX) in the 2020-2021 period. The population in this study are banks registered on the IDX during 2020-2021. 40 banks were selected as research samples using the purposive sampling method. The data used is annual report data and stock transaction summaries from the IDX website. The data analysis technique used is panel data regression processed with the Eviews program. The research results show that credit risk has a significant negative effect on company value, capital has a significant positive effect on company value, while operational risk, liquidity risk, good corporate governance, earnings and earnings management have no effect on company value